허리의 분절적 가동기법이 만성 허리통증 환자의 근육 특성과 안정성 한계에 미치는 영향 - 양대중; 엄요한; Yang, Daejung; Uhm, Yohan (Journal of the Korean Society of Integrative Medicine, 2020)
Purpose : The purpose of this study is to examine the effect of the segmental mobilization technique of the lower back on the characteristics of the muscles and limited of stability of chronic backache patients. Methods : The subjects of the study were 30 chronic back pain patients who were divided into groups of 15, a manual therapy group (Group I) and a spinal decompression therapy group (Group II), via random assignation. The subjects had 15 minutes of superficial heat therapy, 15 minutes of interference wave therapy, and 5 minutes of ultrasound therapy for conservative physical therapy. Additionally, manual therapy and spinal decompression therapy were administered to each group for 30 minutes, 5 times a week for 8 weeks. Before intervention, the characteristics of the muscles and limited of stability of the muscles were analyzed. After 8 weeks of intervention, the above items were re-measured in the same manner and analyzed between groups. Results : The results of comparative analysis of the characteristics of the muscles and limited of stability between groups showed that there were statistically significant differences. The manual therapy group (Group I) showed significant differences in characteristics of the muscles compared to the spinal decompression therapy group (Group II). The manual therapy group (Group I) showed significant differences in limited of stability compared to the spinal decompression therapy group (Group II). Conclusion : The result confirmed that manual therapy was more effective in the characteristics of the muscles and limited of stability. Based on this study, additional studies are necessary on the effect of various techniques of manual therapy on muscle activity and muscle thickness in chronic back pain patients. In order to develop an effective manual therapy program, studies using a variety of evaluations are needed.